Numerical analysis of the penetration process of a 30mm armor-piercing fin-stabilized discarding sabot projectile - Predrag R. Pantović; Aleksandar V. Kari; Aleksa D. Aničić; Miroslav M. Živković; Vladimir P. Milovanović (Vojnotehnički Glasnik, 2024)
Introduction/purpose: In recent times, with the tendency to develop new types of armor-piercing ammunition, constant investments in the development of new types of armored obstacles is necessary. Obstacles made of high-alloy steel plates are still the best form of protection against larger caliber ammunition. There are a number of factors to consider when selecting an alloy, including the weight, dimensions, intended use, desired ballistic performance, and costs. According to that, a numerical analysis of penetration of a 30mm armor-piercing fin-stabilized discarding sabot projectile into the steel alloy Weldox 460 plates of different thicknesses at a distance of 1000m with a velocity of 1300m/s is presented in this paper. Methods: The stresses and deformations of the penetration effect were calculated through numerical analysis and finite element modeling. To specify material characteristics, the Johnson-Cook material model and the fracture of materials model have been utilized. In order to define models and carry out numerical calculations, the software packages FEMAP and LS Dyna have been used in this paper. Results: For a numerical analysis of the penetration process of this projectile type against armor obstacle, four different armor plate thicknesses are calculated: 10mm, 50mm, 100mm, and 110mm. For each of them, the results are shown in a form of stress and displacement, so that the interaction phenomena between the sub-projectile and the armor plate can be described. Conclusion: Modeling the impact on armor-piercing obstacles is extremely difficult, time-consuming, and complex, and the resulting models very successfully (or with some deviation) approximate the real problem of projectile penetration. One of the most effective methods for solving problems of this kind and others of a similar nature in recent times is the finite element method analysis. The material and the target dimensions, as well as the ballistic parameters and the material of the projectile have the biggest influence on projectile penetration. The target's resistance to penetration increases when all input parameters are maintained at the same level and its thickness is increased, and vice versa.